'The Swedish Strategy' to COVID-19 Pandemic:Impact on Vulnerable and Marginalised Communities. Issue 2 (June 2020) - Rambaree, Komalsingh; Nässén, Nessica
All around the world the COVID-19 pandemic is having an enormous impact on people's lives. Contrary to many other countries, Sweden has opted against lockdown. The Swedish Government has put trust in its people and has advised them to be responsible and follow the recommendations and guidelines of the Public Health Agency of Sweden. Using the Interest Theory of Rights, this article discusses the impact of the Swedish response to COVID-19 on three different Swedish communities, and considers the implications of such a strategy on social development. Data was collected from different national and international media sources as well as from Swedish authorities' websites. A qualitative content analysis was used to analyse the data with the help of ATLAS-ti.8.4. The findings section discusses how three community groups in Sweden—the elderly, immigrants from marginalised areas and prisoners—are having their rights altered during this pandemic period. It also outlines different social development approaches being used in Sweden for tackling the challenges relating to the COVID-19 pandemic. This article concludes that a strong democratic state is vital in managing a pandemic such as COVID-19. It also argues that the strength of a state largely depends on its citizens' willpower to take ownership of responsibilities—both individually and collectively.